Integrative taxonomy reveals Europe's rarest songbird species, the Gran Canaria blue chaffinch Fringilla polatzeki. (7th December 2015) - Sangster, George; Rodríguez‐Godoy, Felipe; Roselaar, C. S.; Robb, Magnus S.; Luksenburg, Jolanda A.
Abstract : The conservation of endangered taxa often critically depends on accurate taxonomic designations. The status of the Gran Canaria population of the blue chaffinch Fringilla teydea polatzeki has not been reevaluated since the early 1900s when this taxon was described as a subspecies and combined with the much more common Tenerife blue chaffinch F. t. teydea in a single species. We show that multiple diagnostic differences in plumage, songs, calls and morphometrics distinguish F. t. polatzeki from F. t. teydea . Preliminary playback experiments suggest that F. t. polatzeki is able to discriminate between songs of both taxa. Along with previously reported differences in mitochondrial DNA, these findings show that the blue chaffinches on Gran Canaria and Tenerife represent two distinctive species: F. polatzeki and F. teydea . Gran Canaria blue chaffinch is Europe's rarest passerine species and should be classified as critically endangered. Its long‐term survival in the wild currently depends on a very small (< 20 km 2 ) area in southwest Gran Canaria. Reclassification of Gran Canaria blue chaffinch as a species increases the urgency of ongoing conservation efforts. Our study underscores the critical importance of taxonomic clarification of threatened taxa that are currently classified as 'subspecies'.